(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The formation of economic literacy in primary school students is a critical task in modern education. Future primary school teachers must be equipped with effective methods and tools to instill basic financial and economic concepts in young learners. This article examines practical strategies, including interactive games, project-based learning, digital tools, and collaboration with parents, to enhance economic literacy. It also highlights challenges in teacher training and proposes solutions to integrate economic education into primary curricula. The study emphasizes the importance of preparing educators to foster responsible financial behavior in students from an early age.